Relationship Between PTEN Gene Pathway and Breast Cancer - Demet Akdeniz; Şeref Buğra Tunçer; Hülya Yazıcı (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Breast cancer is the most common malignancy with a high mortality in females worldwide. Phosphatase and tensin homolog (PTEN) is a tumor suppressor gene located on chromosomal band 10q23 and regulates many cellular functions including cell growth, proliferation, and migration. Somatic deletions and/or mutations of PTEN gene is commonly seen in several cancers including breast cancer. PTEN mutations have been found in only 5% of sporadic breast cancers. Germline mutations of the PTEN gene are associated with a rare, autosomal-dominant, familial cancer syndrome known as Cowden disease, which is associated with a 25 to 50% lifetime risk of developing breast cancer. In families with Cowden sendrome, 80% have PTEN germline mutations. The high frequency of loss of heterozygosity in 10q23 and the loss of protein expression without a comparable mutational status suggest there should be other inactivation mechanisms of the PTEN gene. Epigenetic events, such as hypermethylation of cytosine-guanine (CpG) sites in the promoter region, could be one mechanism. PTEN inhibits the phosphatidylinositol 3-kinase/protein kinase B pathway, whose inhibition eventually reduces cell growth and cell proliferation. PTEN loss is highly associated with BRCA1 breast cancers, which could result from genome instability involving homozygous deletions, DNA double-strand breaks and so on. Further detailed mechanistic understanding of the roles of PTEN in DNA repair and DNA damage response in different tissues and cell types will help us fully understand the pre- cise molecular mechanisms by which PTEN maintains genomic stability and contributes to tumor suppression and therapeutic efficacy. Understanding the connection between tumor suppressor BRCA1 and PTEN would facilitate the development of effective agents and strategies to better treatment against cancer. The main purpose of our preparation of this review to emphasize the importance of PTEN gene in breast cancer and PTEN pathway and the development of new targeted therapies in breast cancer by explaining the relationship between this pathway and other pathways.